Exploring Fingerprints of the Extreme Thermoacidophile Metallosphaera sedula Grown on Synthetic Martian Regolith Materials as the Sole Energy Sources - Kölbl, Denise; Pignitter, Marc; Somoza, Veronika; Schimak, Mario P.; Strbak, Oliver; Blazevic, Amir; Milojevic, Tetyana (Frontiers in Microbiology, 2017)
The biology of metal transforming microorganisms is of a fundamental and applied importance for our understanding of past and present biogeochemical processes on Earth and in the Universe. The extreme thermoacidophile Metallosphaera sedula is a metal mobilizing archaeon, which thrives in hot acid environments (optimal growth at 74°C and pH 2.0) and utilizes energy from the oxidation of reduced metal inorganic sources. These characteristics of M. sedula make it an ideal organism to further our knowledge of the biogeochemical processes of possible life on extraterrestrial planetary bodies. Exploring the viability and metal extraction capacity of M. sedula living on and interacting with synthetic extraterrestrial minerals, we show that M. sedula utilizes metals trapped in the Martian regolith simulants (JSC Mars 1A; P-MRS; S-MRS; MRS07/52) as the sole energy sources. The obtained set of microbiological and mineralogical data suggests that M. sedula actively colonizes synthetic Martian regolith materials and releases free soluble metals. The surface of bioprocessed Martian regolith simulants is analyzed for specific mineralogical fingerprints left upon M. sedula growth. The obtained results provide insights of biomining of extraterrestrial material as well as of the detection of biosignatures implementing in life search missions.